ALLANITE-(LA) FROM BUCA DELLA VENA MINE, APUAN ALPS, ITALY, AN EPIDOTE-GROUP MINERAL - Orlandi P.; Pasero M. (My University, 2006)
Allanite-(La) is a member of the epidote group. It was sampled at Buca della Vena mine, near Stazzema, Apuan Alps, Tuscany, Italy. It occurs as Prismatic crystal up to 2-3 mm in length along [010] within barite veins cutting a dolomitic metamorphosed limestone. The mineral is black with brownish reflections, a brown streak and a vitreous luster, transparent to translucent, non-flourescent, brittle with a conchoidal fracture. The observed forms are {001}, {100}, {100}, {101}, {210}, {011}, and the cleavege is imperfect along {001}. The hardness (Mohs) is about 6, D(obs.) 3.93(1), D(calc.) 3.94 g/cm3. Optically, allanite-(La) is biaxial, with nx = 1.755(5), ny = 1.760(5), nz, = 1.765(5), 2V = 90(2)°, very high dispersion and strong pleochroism from greenish to greenish brown. The chemical composition of allanite-(La) has been determined by electron-microprobe analysis and points to the following empirical formula: Ca1.000[(La0.288Ce0.206 Nd0.116Pr0.106 Y0.001)Σ0.717Ca0.279 Th0.006]Σ1.002(Al0.899 Fe3+0.101)Σ1.000 Al1.000(Fe2+0.669 Fe3+0.279Mg0.044 Ti0.007)Σ0.999[(Si0.978 Al0.022)Σ1.000O4] (Si2 O7) O (OH). The simplified formula is Ca(REE,Ca) Al2(Fe2+, Fe3+)(SiO4) (Si2O7)O(OH) (Z = 2). The six strongest lines in the X-ray powder-diffraction pattern [d in Å(I)(hkl)] are: 3.506(20)(2̄11), 2.901(100)(1̄13), 2.860(40)(020), 2.692(60)(013), 2.611(50)(3̄11), and 2.174(25)(4̄01). Allanite-(La) is mono-clinic. P21/m, with a 8.914(4), b 5.726(1), c 10.132(6) Å, ß 114.87(5)°, V 469.1(3) Å3. The crystal structure of allanite-(La) has been refined to R = 0.0328 for 1985 independent reflections collected via single-crystal X-ray-diffraction measurements. The name allanite-(La) recalls the relationship with allanite-(Ce), the Levinson modifier indicating the dominant REE. The root name honors the Scottish mineralogist Thomas Allan (1777-1883). Although the name allanite-(La) has been already used in the literature, the mineral had not been officially approved. The recognition and complete characterization of allanite-(La) from Buca della Vena mine, which now has to be considered the type locality of the mineral, fill a gap in the systematics of the epidote group.
Keywords: ALLANITE-(LA); BUCA DELLA VENA MINE; CRYSTAL STRUCTURE; ELECTRON-MICROPROBE DATA; EPIDOTE GROUP; ITALY; LANTHANUM; NEW MINERAL SPECIES; X-RAY POWDER DATA